The Application of Question Answer Relationship Strategy (QARS) to Increase Students’ Reading Comprehension at SMA Negeri 3 Tondano - Loho, Putri Talita; Muntuuntu, Meity; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study aimed to determine whether the application of Question Answer Relationship Strategy (QARS) can enhance students' reading comprehension. This study was conducted at SMA Negeri 3 Tondano. Employing a quantitative research method through pre-experimental design with a one group pre-test and post-test, the research examines the reading comprehension of class XI Bahasa students during the 2022/2023 academic year, as the subject of this study, which consist of 24 students. Data analysis involved comparing the mean scores of the pre-test and post-test to determine the effectiveness of QARS. The findings revealed a notable enhancement in the mean score from the pre-test (51.3) to the post-test (83.3). The outcomes show a clear improvement in student performance after the application of the Question Answer Relationship strategy. Through the results of this study, it can be concluded that the application of the Question Answer Relationship Strategy is able to increase students of class XI Bahasa at SMA Negeri 3 Tondano reading comprehension.